PERENCANAAN ULANG STRUKTUR GEDUNG SMA NEGERI 1 LUBUK SIKAPING KABUPATEN PASAMAN - Putra, Randi; Masril, Masril; Susanti Yusman, Ana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
In line with the development of Science and Technology (IPTEK), especially in the field of Civil Engineering, building construction is currently also developing very rapidly. In the construction of a building, construction must be produced with sufficient capacity, good quality and efficient implementation. In West Sumatra itself, the need for housing and office buildings as well as the construction of educational facilities is currently experiencing very rapid development. Like the